Steel truss-concrete composite beam
By using microcapsule structural expansion agent in steel truss-concrete composite beams, the problem of poor interface bonding caused by concrete shrinkage deformation is solved, the low self-shrinkage rate and high compressive strength of concrete are achieved, and the bearing capacity and safety of the structure are improved.
Patent Information
- Application Number
- CN202411546722.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-31
AI Technical Summary
After the concrete is poured, the existing steel truss-concrete composite beams have poor interface bonding between the concrete prefabricated plates and the steel trusses and internal steel bars after concrete casting, which easily leads to problems of de-emphasis and de-adhesion, affecting the bearing capacity and safety.
Using a microcapsule structural expansion agent, a microcapsule structural expansion agent with hydrophobic polyion liquid as a bi material is prepared by mixing iron tailings sand, calcium carbonate, coal gangue and phosphogypsum and sintering it, and combined with other raw materials in the concrete to form an integrated cast concrete prefabricated plate.
By matching the self-expansion process of the microcapsule structural expansion agent with the shrinkage process of the concrete, the self-shrinkage rate and volume change effect of the concrete is reduced, the compressive strength and interface combination of the concrete are improved, and the bearing capacity and safety of the structure are enhanced.
Smart Images

Figure CN119571969A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of structural engineering, in particular to a steel truss-concrete composite beam. Background Art
[0002] The combination of steel trusses and precast concrete panels can achieve the advantages of rapid construction and prefabrication and assembly. However, after the concrete is poured, the precast concrete panels are in direct contact with the steel trusses. Due to the shrinkage and deformation of the concrete itself (mainly autogenous shrinkage and temperature shrinkage), the interface between the precast concrete panels and the steel trusses and the internal steel bars is poor, which can easily lead to serious problems of voiding and debonding. This directly affects the bearing capacity of the structure and the composite elastic modulus of concrete, thereby affecting the safety of the structure and whether it can work normally. Although the addition of expansion agents can offset the shrinkage of concrete to a certain extent, the expansion rate of existing expansion agents is often difficult to match with the strength development and shrinkage rate of concrete, resulting in unsatisfactory use results. Summary of the invention
[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a steel truss-concrete composite beam.
[0004] The technical solutions adopted are as follows:
[0005] A steel truss-concrete composite beam, comprising a steel truss and a precast concrete slab, wherein the precast concrete slab is integrally cast by concrete and steel bars;
[0006] The concrete is prepared from the following raw materials in parts by weight:
[0007] 700-800 parts of cement, 200-400 parts of crushed stone, 600-800 parts of sand, 100-150 parts of fly ash, 80-120 parts of steel fiber, 50-80 parts of expansion agent, 1-5 parts of early strength agent, 10-15 parts of polycarboxylate water reducer, and 180-220 parts of water;
[0008] The raw materials for preparing the expansion agent include iron tailings sand, calcium carbonate, coal gangue and phosphogypsum.
[0009] Furthermore, the mass ratio of the iron tailings sand, calcium carbonate, coal gangue and phosphogypsum is 15-30:40-60:15-30:5-10.
[0010] Furthermore, the expansion agent is a microcapsule structure, and the wall material of the microcapsule structure is a hydrophobic polyionic liquid.
[0011] Furthermore, the hydrophobic polyionic liquid is any one of poly 1-vinyl-3-ethyl imidazolium hexafluorophosphate, poly 1-vinyl-3-propyl imidazolium hexafluorophosphate, poly 1-vinyl-3-butyl imidazolium hexafluorophosphate, poly 1-vinyl-3-ethyl imidazolium tetrafluoroborate, poly 1-vinyl-3-propyl imidazolium tetrafluoroborate, and poly 1-vinyl-3-butyl imidazolium tetrafluoroborate, or a combination of two or more thereof.
[0012] Furthermore, the preparation method of the expansion agent is as follows:
[0013] The iron tailings, calcium carbonate, coal gangue and phosphogypsum are mixed and ball-milled, dried, passed through a 200-mesh sieve and pressed into sheets, and then sintered at 1200-1400°C for 1-3 hours. The sintered sheets are crushed to obtain core materials, and the core materials are stirred and dispersed in DMF under nitrogen protection. Divinylbenzene, ionic liquid monomer and free radical initiator are then added, stirred evenly, and reacted in a water bath at 50-70°C for 24-48 hours. After the reaction is completed, the product is collected and dried.
[0014] Furthermore, the iron tailings sand is activated with organic acid in advance.
[0015] Furthermore, the organic acid is any one of citric acid, oxalic acid and malic acid, or a combination of two or more thereof.
[0016] Further, the method of organic acid activation is as follows:
[0017] Prepare the organic acid into a solution, add the iron tailings, heat and evaporate the water, collect the solid, put it into an oven and keep it at 40-80℃ for 10-20h, take it out and wash it with clean water until it is neutral, dry it, heat it to 600-800℃ and calcine it for 1-5h.
[0018] Furthermore, the early strength agent is an alcoholamine early strength agent.
[0019] Furthermore, the steel truss includes two upper chords and one lower chord, the two ends of the two upper chords are connected by a cross bar, the upper chord and the lower chord are connected by straight webs at both ends and an inclined web in the middle, and the upper chord is fixed to the concrete precast plate by rivets.
[0020] Beneficial effects of the present invention:
[0021] The present invention provides a steel truss-concrete composite beam, comprising a steel truss and a concrete precast panel, wherein the concrete precast panel is cast in one piece by concrete and steel bars, the concrete has excellent compressive strength, and has a low self-shrinkage rate, and has a small volume change during the curing process, and will not cause abnormal interface bonding between the concrete precast panel and the steel truss and the internal steel bars due to excessive shrinkage deformation of the concrete itself, thereby affecting the bearing capacity;
[0022] The chemical composition of iron tailings contains Fe2O3, SiO2, SO2, Al2O3, etc., which are commonly used ingredients for preparing expansion agents. The generation of C2(A,F) etc. provides Al, Si, Ca, S etc., while calcium carbonate, coal gangue and phosphogypsum can make up for the lack of CaO, Al2O3 and CaSO4, and turn waste into treasure, consuming solid waste coal gangue and phosphogypsum. When the expansion agent is mixed with silicate cement and undergoes hydration reaction, it generates calcium sulfonate, which expands in volume, offsets the volume shrinkage of concrete, compensates for the shrinkage and cracking of concrete, and improves mechanical properties.
[0023] Organic acid activation treatment of iron tailings can promote the dissolution of Si and Al in iron tailings, destroy the microstructure of iron tailings, make the mixed sintering reaction with calcium carbonate, coal gangue and phosphogypsum more complete, and promote The formation of minerals such as C2(A,F) uses hydrophobic polyionic liquid as the wall material and SO4 in concrete 2- 、CO3 2- , CI - After the anions of the isocyanate are exchanged with those of the hydrophobic polyionic liquid, the wall material can be changed from hydrophobic to hydrophilic, and the core material can be gradually released and expanded. The release and expansion process of the core material can be controlled by coating the wall material, so that the self-expansion process of the microcapsule structure expansion agent is matched with the shrinkage process of the concrete, so that the concrete has a smaller self-shrinkage rate and volume change effect, avoiding the premature weakening or even disappearance of the expansion effect of the expansion agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the structure of a steel truss-concrete composite beam in Example 1 of the present invention, in which the reference numerals represent:
[0025] 1- Precast concrete slab, 2- Upper chord, 3- Lower chord, 4- Straight web, 5- Inclined web, 6- Cross bar. DETAILED DESCRIPTION
[0026] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0027] Cement: Conch P·O 42.5 type silicate cement;
[0028] Gravel: 5-16mm grade gravel;
[0029] Sand: Zone II river sand, fineness modulus 2.8;
[0030] Fly ash: Grade I fly ash
[0031] Steel fiber: end hook type, diameter 0.75mm, length 40mm, Taian Hongtong New Materials Co., Ltd.;
[0032] Microcapsule structure expansion agent: homemade;
[0033] Iron tailings sand: comes from an iron ore mining area, and its composition is shown in Table 1 below:
[0034] Table 1: / wt%
[0035]
[0036] Triethanolamine: Jinan Zesheng Chemical Co., Ltd.;
[0037] Polycarboxylate water reducer: solid content 40%, Jinan Quanchi New Materials Co., Ltd.;
[0038] Water: tap water.
[0039] Embodiment 1:
[0040] This embodiment provides a steel truss-concrete composite beam, including a steel truss and a precast concrete panel 1;
[0041] The steel truss includes two upper chords 2 and one lower chord 3. The two ends of the two upper chords 2 are connected by a cross bar 6. The upper chord 2 and the lower chord 3 are connected by straight webs 4 at both ends and an inclined web 5 in the middle. The upper chord 2 is fixed to the concrete precast slab 1 by rivets.
[0042] The precast concrete panel 1 is cast by integrally pouring concrete and steel bars. The concrete is prepared from the following raw materials in parts by weight:
[0043] 750 parts of cement, 230 parts of crushed stone, 770 parts of sand, 125 parts of fly ash, 110 parts of steel fiber, 60 parts of microcapsule structure expansion agent, 3 parts of triethanolamine, 12 parts of polycarboxylate water reducer, and 210 parts of water;
[0044] Wherein, the preparation method of the microcapsule structure expansion agent is as follows:
[0045] The oxalic acid was prepared into a 0.15 mol / L aqueous solution, and then the iron tailings were added in a solid-liquid mass ratio of 1:5. The mixed solution was heated to 80°C to evaporate the water, and then the solid was collected and placed in an oven at 60°C for 15 hours. The solid was taken out and washed with clean water until neutral and then dried. The solid was placed in a muffle furnace and heated to 800°C for calcination for 2 hours to obtain the activated iron tailings. The activated iron tailings, calcium carbonate, coal gangue and phosphogypsum in a mass ratio of 25:50:18:6 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. The mixed solution was ball milled for 10 hours and then dried. After passing through a 200-mesh sieve, the mixture was sieved. The product was pressed into tablets and then sintered at 1250°C for 2h. The sintered sheets were ground to obtain core materials. The core materials were dispersed in DMF according to a solid-liquid mass ratio of 1:10 and protected with nitrogen. Divinylbenzene, 1-vinyl-3-ethylimidazole hexafluorophosphate and free radical initiator AIBN were added. The mass ratio of core material, divinylbenzene, 1-vinyl-3-ethylimidazole hexafluorophosphate and free radical initiator AIBN was 10:0.04:1:0.001. After stirring evenly, the reaction was stirred in a water bath at 60°C for 24h. After the reaction was completed, the product was collected and dried.
[0046] Embodiment 2:
[0047] This embodiment provides a steel truss-concrete composite beam, including a steel truss and a precast concrete panel 1;
[0048] The steel truss includes two upper chords 2 and one lower chord 3. The two ends of the two upper chords 2 are connected by a cross bar 6. The upper chord 2 and the lower chord 3 are connected by straight webs 4 at both ends and an inclined web 5 in the middle. The upper chord 2 is fixed to the concrete precast slab 1 by rivets.
[0049] The precast concrete panel 1 is cast by integrally pouring concrete and steel bars. The concrete is prepared from the following raw materials in parts by weight:
[0050] 750 parts of cement, 230 parts of crushed stone, 770 parts of sand, 125 parts of fly ash, 110 parts of steel fiber, 60 parts of microcapsule structure expansion agent, 3 parts of triethanolamine, 12 parts of polycarboxylate water reducer, and 210 parts of water;
[0051] Wherein, the preparation method of the microcapsule structure expansion agent is as follows:
[0052] Prepare 0.15 mol / L oxalic acid aqueous solution, add iron tailings in a solid-liquid mass ratio of 1:5, heat the mixed solution to 80°C, evaporate the water, collect the solid, put it in an oven and keep it at 60°C for 15 hours, take it out and wash it with clean water until it is neutral, then dry it, and then place it in a muffle furnace and heat it to 800°C and calcine it for 2 hours to obtain activated iron tailings. Add activated iron tailings, calcium carbonate, coal gangue and phosphogypsum in a mass ratio of 30:60:30:10 into a ball mill, use anhydrous ethanol as the ball milling medium, mix and ball mill for 10 hours, then dry it and pass it through a 200-mesh sieve. The product was then tableted and sintered at 1250°C for 2 hours. The sintered sheet was ground to obtain the core material. The core material was dispersed in DMF according to the solid-liquid mass ratio of 1:10 and protected by nitrogen. Divinylbenzene, 1-vinyl-3-ethylimidazole hexafluorophosphate and free radical initiator AIBN were added. The mass ratio of core material, divinylbenzene, 1-vinyl-3-ethylimidazole hexafluorophosphate and free radical initiator AIBN was 10:0.04:1:0.001. After stirring evenly, the reaction was stirred in a water bath at 60°C for 24 hours. After the reaction was completed, the product was collected and dried.
[0053] Embodiment 3:
[0054] This embodiment provides a steel truss-concrete composite beam, including a steel truss and a precast concrete panel 1;
[0055] The steel truss includes two upper chords 2 and one lower chord 3. The two ends of the two upper chords 2 are connected by a cross bar 6. The upper chord 2 and the lower chord 3 are connected by straight webs 4 at both ends and an inclined web 5 in the middle. The upper chord 2 is fixed to the concrete precast slab 1 by rivets.
[0056] The precast concrete panel 1 is cast by integrally pouring concrete and steel bars. The concrete is prepared from the following raw materials in parts by weight:
[0057] 750 parts of cement, 230 parts of crushed stone, 770 parts of sand, 125 parts of fly ash, 110 parts of steel fiber, 60 parts of microcapsule structure expansion agent, 3 parts of triethanolamine, 12 parts of polycarboxylate water reducer, and 210 parts of water;
[0058] Wherein, the preparation method of the microcapsule structure expansion agent is as follows:
[0059] The oxalic acid was prepared into a 0.15 mol / L aqueous solution, and then the iron tailings were added in a solid-liquid mass ratio of 1:5. The mixed solution was heated to 80°C to evaporate the water, and then the solid was collected and placed in an oven at 60°C for 15 hours. The solid was taken out and washed with clean water until neutral and then dried. The solid was placed in a muffle furnace and heated to 800°C for calcination for 2 hours to obtain the activated iron tailings. The activated iron tailings, calcium carbonate, coal gangue and phosphogypsum in a mass ratio of 15:40:15:5 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. The mixture was ball milled for 10 hours and then dried. After passing through a 200-mesh sieve, the mixture was sieved. The product was pressed into tablets and then sintered at 1250°C for 2h. The sintered sheets were ground to obtain core materials. The core materials were dispersed in DMF according to a solid-liquid mass ratio of 1:10 and protected with nitrogen. Divinylbenzene, 1-vinyl-3-ethylimidazole hexafluorophosphate and free radical initiator AIBN were added. The mass ratio of core material, divinylbenzene, 1-vinyl-3-ethylimidazole hexafluorophosphate and free radical initiator AIBN was 10:0.04:1:0.001. After stirring evenly, the reaction was stirred in a water bath at 60°C for 24h. After the reaction was completed, the product was collected and dried.
[0060] Embodiment 4:
[0061] This embodiment provides a steel truss-concrete composite beam, including a steel truss and a precast concrete panel 1;
[0062] The steel truss includes two upper chords 2 and one lower chord 3. The two ends of the two upper chords 2 are connected by a cross bar 6. The upper chord 2 and the lower chord 3 are connected by straight webs 4 at both ends and an inclined web 5 in the middle. The upper chord 2 is fixed to the concrete precast slab 1 by rivets.
[0063] The precast concrete panel 1 is cast by integrally pouring concrete and steel bars. The concrete is prepared from the following raw materials in parts by weight:
[0064] 800 parts of cement, 400 parts of crushed stone, 800 parts of sand, 150 parts of fly ash, 120 parts of steel fiber, 80 parts of microcapsule structure expansion agent, 5 parts of triethanolamine, 15 parts of polycarboxylate water reducer, and 220 parts of water;
[0065] Wherein, the preparation method of the microcapsule structure expansion agent is as follows:
[0066] The oxalic acid was prepared into a 0.15 mol / L aqueous solution, and then the iron tailings were added according to the solid-liquid mass ratio of 1:5. The mixed solution was heated to 80 ° C and the water was evaporated to collect the solid, put into an oven and kept at 60 ° C for 15 hours, taken out and washed with clean water until neutral and then dried, and then placed in a muffle furnace and heated to 800 ° C for calcination for 2 hours to obtain activated iron tailings. The activated iron tailings, calcium carbonate, coal gangue and phosphogypsum with a mass ratio of 15-30:40-60:15-30:5-10 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. The mixed ball mill was dried after 10 hours, and then passed through 2 00 mesh sieve, and then sintered at 1250℃ for 2h, and the sintered sheet was ground to get the core material, and the core material was dispersed in DMF according to the solid-liquid mass ratio of 1:10 and protected by nitrogen, and then divinylbenzene, 1-vinyl-3-ethylimidazole hexafluorophosphate and free radical initiator AIBN were added, and the mass ratio of core material, divinylbenzene, 1-vinyl-3-ethylimidazole hexafluorophosphate and free radical initiator AIBN was 10:0.04:1:0.001. After stirring evenly, stir and react in a water bath at 60℃ for 24h. After the reaction, collect the product and dry it.
[0067] Embodiment 5:
[0068] This embodiment provides a steel truss-concrete composite beam, including a steel truss and a precast concrete panel 1;
[0069] The steel truss includes two upper chords 2 and one lower chord 3. The two ends of the two upper chords 2 are connected by a cross bar 6. The upper chord 2 and the lower chord 3 are connected by straight webs 4 at both ends and an inclined web 5 in the middle. The upper chord 2 is fixed to the concrete precast slab 1 by rivets.
[0070] The precast concrete panel 1 is cast by integrally pouring concrete and steel bars. The concrete is prepared from the following raw materials in parts by weight:
[0071] 700 parts of cement, 200 parts of crushed stone, 600 parts of sand, 100 parts of fly ash, 80 parts of steel fiber, 50 parts of microcapsule structure expansion agent, 1 part of triethanolamine, 10 parts of polycarboxylate water reducer, and 180 parts of water;
[0072] Wherein, the preparation method of the microcapsule structure expansion agent is as follows:
[0073] The oxalic acid was prepared into a 0.15 mol / L aqueous solution, and then the iron tailings were added according to the solid-liquid mass ratio of 1:5. The mixed solution was heated to 80 ° C and the water was evaporated to collect the solid, put into an oven and kept at 60 ° C for 15 hours, taken out and washed with clean water until neutral and then dried, and then placed in a muffle furnace and heated to 800 ° C for calcination for 2 hours to obtain activated iron tailings. The activated iron tailings, calcium carbonate, coal gangue and phosphogypsum with a mass ratio of 15-30:40-60:15-30:5-10 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. The mixed ball mill was dried after 10 hours, and then passed through 2 00 mesh sieve, and then sintered at 1250℃ for 2h, and the sintered sheet was ground to get the core material, and the core material was dispersed in DMF according to the solid-liquid mass ratio of 1:10 and protected by nitrogen, and then divinylbenzene, 1-vinyl-3-ethylimidazole hexafluorophosphate and free radical initiator AIBN were added, and the mass ratio of core material, divinylbenzene, 1-vinyl-3-ethylimidazole hexafluorophosphate and free radical initiator AIBN was 10:0.04:1:0.001. After stirring evenly, stir and react in a water bath at 60℃ for 24h. After the reaction, collect the product and dry it.
[0074] Comparative Example 1:
[0075] The method is basically the same as Example 1, except that no microcapsule structure expansion agent is added.
[0076] Comparative Example 2:
[0077] The method is basically the same as Example 1, except that the core material is directly used as the expansion agent;
[0078] The preparation method of the expansion agent is as follows:
[0079] Prepare 0.15 mol / L oxalic acid into an aqueous solution, then add iron tailings in a solid-liquid mass ratio of 1:5, heat the mixed solution to 80°C to evaporate the water, collect the solid, put it in an oven and keep it at 60°C for 15 hours, take it out, wash it thoroughly with clean water until it is neutral, and then dry it, then put it in a muffle furnace and heat it to 800°C and calcine it for 2 hours to obtain activated iron tailings, add activated iron tailings, calcium carbonate, coal gangue and phosphogypsum in a mass ratio of 25:50:18:6 into a ball mill, use anhydrous ethanol as the ball milling medium, mix and ball mill for 10 hours and then dry, pass through a 200-mesh sieve and press it into sheets, then sinter at 1250°C for 2 hours, and grind the fired sheets into powder.
[0080] Comparative Example 3:
[0081] The method is basically the same as Example 1, except that the commercially available HP-CSA expansion agent is used instead of the microcapsule structure expansion agent.
[0082] Performance Test:
[0083] ① The concrete in Examples 1-5 and Comparative Examples 1-3 were made into test specimens according to GB / T 17671-2021 “Test Method for Strength of Cement Mortar”, and 3 specimens were prepared in each group. The compressive strength (unit: MPa) of the specimens cured to the standard age of 3d, 7d and 28d was measured using a YAW-300 microcomputer-controlled electro-hydraulic servo pressure testing machine. The measurement results were averaged. The test results are shown in Table 2.
[0084] Table 2:
[0085]
[0086]
[0087] As can be seen from Table 2 above, the concrete in the present invention has excellent compressive strength;
[0088] From the comparison of the data of Example 1 and Comparative Example 1, it can be seen that the addition of the microcapsule structure expansion agent plays a positive role in improving the compressive strength of the concrete. It may be that its self-expansion process is compatible with the shrinkage process of the concrete, which reduces the generation of cracks caused by shrinkage stress inside the concrete, thereby improving the compressive strength.
[0089] From the comparison of the data of Example 1 and Comparative Example 2, it can be seen that since the microcapsule structure has a limiting effect on the expansion of the expansion agent, compared with directly adding the core material, the expansion agent with a microcapsule structure has a greater improvement in the later compressive strength of the concrete;
[0090] From the comparison of the data of Example 1 and Comparative Example 3, it can be seen that the commercially available HP-CSA expansive agent has a more obvious improvement on the early compressive strength of concrete. It may be that the early expansion effect of the commercially available HP-CSA expansive agent is sufficient to compensate for the shrinkage of the concrete. However, as time goes on, the expansion effect of the commercially available HP-CSA expansive agent weakens or even disappears, and the concrete continues to shrink. The final compressive strength of the concrete is lower than that of Example 1 in which the microcapsule structure expansive agent is added.
[0091] ② The autogenous shrinkage of the concrete in Examples 1-5 and Comparative Examples 1-3 was measured using a contact bellows tester. The inner diameter of the bellows used in the test was 55 mm, the length was 420 ± 5 mm, and the resolution of the micrometer was 1 μm. Three specimens were prepared for each group, and the average value was taken as the final shrinkage result, and the value was accurate to 1.0 × 10 -6 The autogenous shrinkage test was carried out at a constant temperature of 20±2°C and a constant humidity of 60±5%. The test was based on ASTM C1698-09 "Test method for autogenous shrinkage of cement paste and mortar". The test results are shown in Table 3 below.
[0092] Table 3:
[0093]
[0094] As can be seen from Table 3 above, the concrete in the present invention has a lower autogenous shrinkage rate and a smaller volume change during the curing process;
[0095] From the data comparison of Example 1 and Comparative Example 1, it can be seen that the concrete without the expansion agent has a larger autogenous shrinkage, while after the expansion agent is added, the microcapsule structure expansion agent has a lower autogenous shrinkage rate because the autogenous expansion process of the expansion agent is compatible with the shrinkage process of the concrete.
[0096] From the comparison of the data of Example 1 with Comparative Examples 2 and 3, it can be seen that when the core material or the commercially available HP-CSA expansion agent is directly added, due to its early expansion effect, the self-shrinkage rate at 3d is better than that of the microcapsule structure expansion agent. However, as the expansion effect weakens or even disappears, the self-shrinkage rates at 7d and 28d increase significantly, which makes the volume change of the concrete larger, which is not conducive to the interface bonding with the steel truss.
[0097] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A steel truss-concrete composite beam, characterized in that: It includes a steel truss and a precast concrete panel, wherein the precast concrete panel is integrally cast by concrete and steel bars; The concrete is prepared from the following raw materials in parts by weight: 700-800 parts of cement, 200-400 parts of crushed stone, 600-800 parts of sand, 100-150 parts of fly ash, 80-120 parts of steel fiber, 50-80 parts of expansion agent, 1-5 parts of early strength agent, 10-15 parts of polycarboxylate water reducer, and 180-220 parts of water; The raw materials for preparing the expansion agent include iron tailings sand, calcium carbonate, coal gangue and phosphogypsum.
2. The steel truss-concrete composite beam according to claim 1, characterized in that: The mass ratio of the iron tailings sand, calcium carbonate, coal gangue and phosphogypsum is 15-30:40-60:15-30:5-10.
3. The steel truss-concrete composite beam according to claim 2, characterized in that: The expansion agent is a microcapsule structure, and the wall material of the microcapsule structure is a hydrophobic polyionic liquid.
4. The steel truss-concrete composite beam according to claim 3, characterized in that: The hydrophobic polyionic liquid is any one of poly 1-vinyl-3-ethyl imidazolium hexafluorophosphate, poly 1-vinyl-3-propyl imidazolium hexafluorophosphate, poly 1-vinyl-3-butyl imidazolium hexafluorophosphate, poly 1-vinyl-3-ethyl imidazolium tetrafluoroborate, poly 1-vinyl-3-propyl imidazolium tetrafluoroborate, and poly 1-vinyl-3-butyl imidazolium tetrafluoroborate, or a combination of two or more thereof.
5. The steel truss-concrete composite beam according to claim 4, characterized in that: The preparation method of the swelling agent is as follows: The iron tailings, calcium carbonate, coal gangue and phosphogypsum are mixed and ball-milled, dried, passed through a 200-mesh sieve and pressed into sheets, and then sintered at 1200-1400°C for 1-3 hours. The sintered sheets are crushed to obtain core materials, and the core materials are stirred and dispersed in DMF under nitrogen protection. Divinylbenzene, ionic liquid monomer and free radical initiator are then added, stirred evenly, and reacted in a water bath at 50-70°C for 24-48 hours. After the reaction is completed, the product is collected and dried.
6. The steel truss-concrete composite beam according to claim 5, characterized in that: The iron tailings sand is activated with organic acid in advance.
7. The steel truss-concrete composite beam according to claim 6, characterized in that: The organic acid is any one of citric acid, oxalic acid and malic acid or a combination of two or more thereof.
8. The steel truss-concrete composite beam according to claim 5, characterized in that: The method of the organic acid activation is as follows: Prepare the organic acid into a solution, add the iron tailings, heat and evaporate the water, collect the solid, put it into an oven and keep it at 40-80℃ for 10-20h, take it out and wash it with clean water until it is neutral, dry it, heat it to 600-800℃ and calcine it for 1-5h.
9. The steel truss-concrete composite beam according to claim 1, characterized in that: The early strength agent is an alcoholamine early strength agent.
10. The steel truss-concrete composite beam according to claim 1, characterized in that: The steel truss includes two upper chords and one lower chord, the two ends of the two upper chords are connected by a cross bar, the upper chord and the lower chord are connected by straight webs at both ends and an inclined web in the middle, and the upper chord is fixed to the concrete precast plate by rivets.
Citation Information
Patent Citations
Concrete expansion agent and preparation method thereof
CN104446081A
Cement expansive material produced by using waste resources
CN105271884A
Concrete and preparation technology thereof
CN107572963A
Improvement method for silt loam saline-alkali soil
CN108076715A
Microcapsule composite material and preparation method thereof
CN111589387A